PARASITES AS POTENTIAL STOCK MARKERS FOR TUNA IN INDONESIAN WATERS - Pratiwi Lestari; R.J.G Lester; Craig Proctor (Indonesian Fisheries Research Journal, 2017)
Tuna fish are highly migratory species. Clarifying their stock structures and migration patterns is important for tuna fisheries management. The purpose of this research was to examine the parasites of bigeye tuna (Thunnus obesus) and yellowfin tuna (Thunnus albacares) to determine which parasites may be potential stock markers for assessment of tuna migration patterns. Bigeye tuna and yellowfin tuna were collected (measured between 28-48 cm fork length) from 9 sites across Indonesia and from 2 ‘outlier sites’ (The Maldives and Solomon Islands). Organs including gills (filaments and branchial arches), stomach wall, liver, pyloric caeca, and intestines were examined. Seven types of didymozoids were distinguished including 3 Didymosulcus spp., 4 Kollikeria spp. and one acanthocephalan (Bolbosoma sp.). The results suggest these fish parasites are potentially useful markers for assessment of tuna migration pattern, contributing information needed for fisheries management in Indonesia.